HBx and YAP expression could promote tumor development and progression in HBV-related hepatocellular carcinoma - Chiyumi Oda; Kenya Kamimura; Osamu Shibata; Shinichi Morita; Yuto Tanaka; Toru Setsu; Hiroyuki Abe; Takeshi Yokoo; Akira Sakamaki; Hiroteru Kamimura; Satoshi Kofuji; Toshifumi Wakai; et al. (Biochemistry and Biophysics Reports, 2022)
Background: Hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) accounts for 10%–20% of the total HCC numbers. Its clinical features include the occurrence in the younger generation, large tumors, and poor prognosis. The contribution of hepatitis B virus X (HBx) protein in hepatocytes during activation of various oncogenic pathways has been reported. We aimed to assess the possible association between HBx and Yes-associated protein (YAP) expression in the liver tissue and the clinical features of HBV-related HCC. Methods: The relationship between HBx and YAP expression was examined in vivo using HCC tumor and peritumor tissues (n = 55). The clinical information including tumor size, marker, and the prognosis was assessed with protein expressions. The in vitro gene expression analyses were conducted using HBx- and YAP-overexpressing HCC cell lines. Results: Among 19 cases of HBV-related, 17 cases of hepatitis C virus (HCV)-related, and 19 cases of nonviral-related HCC, the HBV-related tumor showed the largest size. The HBx-stained area in the tumor and peritumor tissue showed a significant correlation with tumor size and serum α-fetoprotein level. YAP expression was higher in HBV-related tumor tissue than in the peritumor tissue and HCV-related tumor. Additionally, HBx and YAP protein expressions are correlated and both expressions in the tumor contributed to the poor prognosis. An in vitro study demonstrated that HBx and YAP overexpression in the hepatocytes activate the various oncogenic signaling pathways. Conclusions: Our study demonstrated that YAP expression in the liver of HBV-infected patients might be the key factor in HBV-related HCC development and control of tumor-related features.